Relación entre la biomasa de jarales y su rendimiento energético por pirolisis - Nuñez E.; Cabeza J.; Escudero J.C. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Energetic yield obtained from 'jara' (Cistus ladanifer L.) was studied through transformation of biomass into char. Pyrolysis, distillation of organic materials by heating without oxygen addition, was utilised. Three different ages of 'jara' were tested. Leaves, capsules, photosynthetic and non-photosynthetic shoots were separately pyrolysed. Char yield and heating value (32-44.9 per cent and 7200 Kcal Kg-1 respectively) were comparable to those obtained from evergreen oak and other trees, under the same experimental conditions. Exploitation of 'jara' as alternative energy source is discussed and related ecological consequences are assessed.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)